Bahasa Inggris sebagai Alat Promosi Pariwisata di Provinsi Sulawesi Tengah: Tinjauan Linguistik dari Perspektif Kajian Pustaka - Irsan Bertinus Tondowala; Yohanis Tarukallo (Journal of Innovative and Creativity, 2025)
This qualitative study explores the role of English as a tool for tourism promotion in Central Sulawesi, Indonesia, through a linguistic perspective using a library research approach. The research identifies how English enhances destination appeal, facilitates cross-cultural communication, and supports digital marketing strategies. Findings reveal that English proficiency among local tourism stakeholders significantly improves service quality and tourist satisfaction. However, limited language skills and perceptions of English as a foreign language pose challenges. Bilingual promotional materials and strategic language use in social media are critical for global outreach. The study recommends language training and optimized digital content to strengthen Central Sulawesi’s tourism competitiveness.